2000
DOI: 10.1039/a907219e
|View full text |Cite
|
Sign up to set email alerts
|

Ground state EDA complex formation between [60]fullerene and a series of polynuclear aromatic hydrocarbons

Abstract: Formation constants of 1 : 1 adducts of [60]fullerene with naphthalene, phenanthrene, anthracene, pyrene and chrysene have been determined in CCl 4 medium. Ionisation potentials of donor molecules and charge transfer (CT) transition energies of the [60]fullerene adducts have been found to correlate in accordance with the Mulliken equation. From such correlation the electron affinity of [60]fullerene has been calculated to be 2.32 eV in solution.A good estimate for the sp 2 C-sp 2 C resonance integral β in benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…In contradiction with these results, substantially larger equilibrium constants were recently reported for the same C 60 systems with values ranging from 0.7 to 66 M -1 , depending on the number of aromatic rings of the donor. 22 In another study, 27 the same authors claim to have identified CT bands in the spectrum of C 60 dissolved in a number of benzene liquid derivatives and report very small equilibrium constants (0.1 to 1.2 M -1 ) but, surprisingly, very significant enthalpies of complex formation (-29 to -98 kJ mol -1 ). Again, in a study of the charge-transfer interaction of C 70 with aromatic hydrocarbons, Bhattacharya et al 25 report high equilibrium constants with values ranging from 11 to 490 M -1 , and significant formation enthalpies with values ranging from -21 to -66 kJ mol -1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contradiction with these results, substantially larger equilibrium constants were recently reported for the same C 60 systems with values ranging from 0.7 to 66 M -1 , depending on the number of aromatic rings of the donor. 22 In another study, 27 the same authors claim to have identified CT bands in the spectrum of C 60 dissolved in a number of benzene liquid derivatives and report very small equilibrium constants (0.1 to 1.2 M -1 ) but, surprisingly, very significant enthalpies of complex formation (-29 to -98 kJ mol -1 ). Again, in a study of the charge-transfer interaction of C 70 with aromatic hydrocarbons, Bhattacharya et al 25 report high equilibrium constants with values ranging from 11 to 490 M -1 , and significant formation enthalpies with values ranging from -21 to -66 kJ mol -1 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] A striking manifestation of the different behavior displayed by fullerenes and by aromatic hydrocarbons toward electron acceptors is the lack of fluorescence quenching of a C 60 dendrimer by Cs + , 26 whereas this same cation efficiently quenches a number of aromatic hydrocarbons by the external heavy-atom effect. In the case of excited-state fullerenes, mixing of the wave functions by charge-transfer to Cs + is not effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The study of CT interaction of imipramine with different acceptors can help to elucidate many chemical and biological phenomena that imipramine participates in. Review of the literature reveals that some spectroscopic and kinetic studies on the interaction of different drugs with DDQ has been reported before, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] but to the best of our knowledge there is not a systematic study on the activation parameters, stability and stoichiometry of the imipramine complex with DDQ.…”
mentioning
confidence: 99%
“…12,13 Recently charge transfer complexes have been gaining importance as potential high efficiency non-linear optical materials. 14 These complexes have been studied in organic conductors and photoconductors.…”
mentioning
confidence: 99%